2016
DOI: 10.1016/j.chemosphere.2016.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Microbial bioavailability of 2,2′,4,4′-Tetrabromodiphenyl ether (BDE-47) in natural sediments from major rivers of China

Abstract: Microbial degradation plays a crucial role in eliminating polybrominated diphenyl ethers (PBDEs) in environments. However, the microbial bioavailability of PBDEs in aquatic sediments is not well understood. In this work, the bioavailability of 2,2',4,4'-tetrabromodiphenyl ether (BDE-47), a typical PBDE congener, to PBDE-degrading microorganisms in natural sediments from six Chinese rivers under anaerobic conditions was investigated. The contents of black carbon (BC) and total organic carbon (TOC) in the six se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Microbial degradation plays a key role in the attenuation of HOCs, and it greatly regulated by solid particles in sediment and soil because of HOCs adsorption on particle surfaces ( Cycoń and Piotrowska-Seget , 2016 ; Cycoń et al, 2017 ; Mansouri et al, 2017 ; Ren et al, 2017 ). Generally, sorbed organic compounds are considered unavailable for microbial degradation without prior desorption ( Bouchez et al, 1995 ; Theng et al, 2001 ; Zhu et al, 2016 ). Bosma et al (1997) suggested that only freely dissolved organic compounds can be taken up by bacterial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial degradation plays a key role in the attenuation of HOCs, and it greatly regulated by solid particles in sediment and soil because of HOCs adsorption on particle surfaces ( Cycoń and Piotrowska-Seget , 2016 ; Cycoń et al, 2017 ; Mansouri et al, 2017 ; Ren et al, 2017 ). Generally, sorbed organic compounds are considered unavailable for microbial degradation without prior desorption ( Bouchez et al, 1995 ; Theng et al, 2001 ; Zhu et al, 2016 ). Bosma et al (1997) suggested that only freely dissolved organic compounds can be taken up by bacterial cells.…”
Section: Introductionmentioning
confidence: 99%